Developing balanced scorecard model for vocational high school education - Apri Winge Adindo (Jurnal Akuntabilitas Manajemen Pendidikan, 2017)
The objective of the study was to find an appropriate Balanced Scorecard model to be implemented in the vocational education management and to test the effectiveness of balanced scorecard internal model for the vocational high school education. The method that the researchers implemented in the study was the research and development designed by Borg Gall. The data in the study were gathered by means of in-depth interview, observation and documentary analysis in the five prominent vocational high schools from the Province of Southeast Sulawesi. The informants in the study were selected by means of snowball sampling. The data validity was tested by the triangulation technique. The First Stage and the Second Stage of model validation/ experiment was implemented by means of Delphi technique and the validation/experiment of both stages involved 50 leaders from the state and the private vocational high schools in the Province of Southeast Sulawesi. The study showed that the appropriate Balanced Scorecard model for the vocational high school educational management has been a system that might be implemented for identifying and for measuring the main performance of vocational high schools through four perspectives namely the financial perspective, the customer perspective, the internal process perspective and the learning and growth perspective. Balanced Scorecard model for the vocational high school education has met the criteria of quite high internal effectiveness model and has belonged to the good criteria. As a result, the Balanced Scorecard model might be implemented as the model of vocational high school managerial implementation.Keyword: balanced scorecard, vocational high school and vocational high school performance PENGEMBANGAN MODEL BALANCED SCORECARD UNTUK PENDIDIKAN SMKAbstrakTujuan penelitian ini adalah mengembangkan model Balanced Scorecard yang cocok untuk diterapkan dalam pengelolaan pendidikan kejuruan dan menguji keefektifan internal model Balanced Scorecard untuk pendidikan SMK. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian dan pengembangan (RD) rancangan Borg Gall. Data penelitian dikumpulkan melalui wawancara mendalam, observasi, dan analisis dokumen pada lima SMK Unggul di Provinsi Sulawesi Tenggara. Informan penelitian ditetapkan dengan snowball sampling. Keabsahan data diuji dengan teknik trianggulasi. Uji coba/validasi model Tahap 1 dan Tahap 2 menggunakan teknik Delphi dengan subjek penelitian sebanyak 50 orang pimpinan SMK dari 15 SMK Negeri dan SMK Swasta di Provinsi Sulawesi Tenggara. Penelitian ini menunjukkan bahwa model Balanced Scorecard yang cocok untuk mengelola manajemen SMK adalah suatu sistem yang digunakan untuk mengenali dan mengukur kinerja utama SMK melalui empat perspektif Balanced Scorecard meliputi perspektif keuangan, pelanggan, proses internal, pembelajaran dan pertumbuhan. Model Balanced Scorecard yang dikembangkan untuk pendidikan SMK yang diajukan telah memenuhi kriteria keefektifan internal model yang tinggi dan termasuk kategori sangat baik, sehingga layak digunakan sebagai model pelaksanaan manajemen SMK.Kata kunci: balanced scorecard, SMK, dan kinerja SMK